Mapping an ethnography of change in teachers of Italian (L2) learning process drama - Piazzoli, Erika (My University, 2016)
This paper discusses a longitudinal, participatory case study focused on a group of experienced teachers of Italian (L2), learning to integrate process drama pedagogy in their practice. Process drama is an embodied approach for second language teaching and learning, focusing on the process (drama workshop), rather than the product (performance) aiming to engage learners in a felt-experience of the target language and culture. The paper reports the final leg of a wider study, and synthesized results on teachers' tacit knowledge, transformed into knowing-in-action, when using process drama with adult students of Italian (L2).
PUBLISHED
http://tilca.qc.cuny.edu/?page_id=26
Keywords: Process drama; Italian L2; Reflection-in-action; Knowing-in-action; Reflective practice; Drama and SLA; Creative Arts Practice; Identities in Transformation; PROCESS DRAMA; Education